RANCANG BANGUN SISTEM HYBRID TENAGA SURYA DAN TENAGA ANGIN SEBAGAI SUMBER ENERGI LISTRIK DI KABUPATEN SIGI - Kalatiku, Protus P; Patadungan, Yosep S; Dodu, Erwin (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2014)
The using of alternative energy as a power source is intended to solve the problems of electricity supply which has not reached the entire region of Central Sulawesi province, especially in Sigi regency. The utilizing of hybrid system of solar and wind power is a solution that can be considered as a source of electrical energy which the solar cell is used as the primary source, whereas wind turbines can be used as a complementary source when solar irradiance cannot meet load requirements. This research aims to design and build alternative sources of electrical energy which is based on hybrid system of solar and wind power by taking into account the geographical factors of place where the system is built.Keywords: hybridsystem of solar and wind power, solar cells, wind turbine.